Proces decentralizacji i podział kompetencji w programowaniu i realizacji polityki publicznej w Hiszpanii na przykładzie Katalonii - Kozłowska, Maja (Polityka i Społeczeństwo, 2020)
In accordance with the Constitution of 1978, Spanish autonomous communities are “equipped with” all features of a composite state (regional parliament, government, autonomous administration) and function on the basis of autonomous statutes approved by the national parliament. The Catalan Statute of 19th July 2006 establishes the division of responsibilities, including exclusive regional competences (agriculture, culture, sport and tourism, spatial planning); shared competences (education, health care, environmental protection, industry, banks and insurances); and executive competences (waterworks, prisons system, intellectual property). The analysis of chosen competences in Catalonia will present the characteristics of autonomy and decentralization in Spain with reference to the attempts to create a regional model of programming and realization of public policies.